B-Type Natriuretic Peptide in the Critically Ill with Acute Kidney Injury - Massimo de Cal; Mikko Haapio; Dinna N. Cruz; Paolo Lentini; Andrew A. House; Ilona Bobek; Grazia M. Virzì; Valentina Corradi; Flavio Basso; Pasquale Piccinni; Angela D'Angelo; Jamie W. Chang; et al. (International Journal of Nephrology)
Introduction. Acute kidney injury (AKI) is common in the intensive care unit (ICU) and associated with poor outcome. Plasma B-type natriuretic peptide (BNP) is a biomarker related to myocardial overload, and is elevated in some ICU patients. There is a high prevalence of both cardiac and renal dysfunction in ICU patients. Aims. To investigate whether plasma BNP levels in the first 48 hours were associated with AKI in ICU patients. Methods. We studied a cohort of 34 consecutive ICU patients. Primary outcome was presence of AKI on presentation, or during ICU stay. Results. For patients with AKI on presentation, BNP was statistically higher at 24 and 48 hours than No-AKI patients (865 versus 148 pg/mL; 1380 versus 131 pg/mL). For patients developing AKI during 48 hours, BNP was statistically higher at 0, 24 and 48 hours than No-AKI patients (510 versus 197 pg/mL; 552 versus 124 pg/mL; 949 versus 104 pg/mL). Conclusion. Critically ill patients with AKI on presentation or during ICU stay have higher levels of the cardiac biomarker BNP relative to No-AKI patients. Elevated levels of plasma BNP may help identify patients with elevated risk of AKI in the ICU setting. The mechanism for this cardiorenal connection requires further investigation.